2017
DOI: 10.1016/j.nicl.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Cingulate cortex functional connectivity predicts future relapse in alcohol dependent individuals

Abstract: Alcohol dependence is a chronic relapsing illness. Alcohol and stress cues have consistently been shown to increase craving and relapse risk in recovering alcohol dependent (AUD) patients. However, differences in functional connectivity in response to these cues have not been studied using data-driven approaches. Here, voxel-wise connectivity is used in a whole-brain investigation of functional connectivity differences associated with alcohol and stress cues and to examine whether these differences are related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 55 publications
6
52
3
Order By: Relevance
“…). Two recent prospective studies reported altered cingulate cortex connectivity during individualized imaginary scripts provoking either alcohol‐, stress‐associated or neutral states in AD . Those patients who showed greater posterior cingulate connectivity during alcohol imagery, or less anterior, mid‐cingulate connectivity during neutral trials, showed longer abstinence during the following 90 days and resembled healthy controls.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…). Two recent prospective studies reported altered cingulate cortex connectivity during individualized imaginary scripts provoking either alcohol‐, stress‐associated or neutral states in AD . Those patients who showed greater posterior cingulate connectivity during alcohol imagery, or less anterior, mid‐cingulate connectivity during neutral trials, showed longer abstinence during the following 90 days and resembled healthy controls.…”
Section: Resultsmentioning
confidence: 98%
“…We found nine relevant fMRI studies investigating the role of cognitive functions seen commonly in AD, such as executive, motivational aspects of behavior and emotion processing (for reviews, see ).…”
Section: Resultsmentioning
confidence: 99%
“…This has been associated with impairment of executive function, reward-directed behavior, and conditioning, all of which have been implicated in impulsivity, compulsive drug use, and addiction [3133]. More recently, Zakiniaeiz et al demonstrated that the cingulate cortex may be a key region in the disruption of functional connectivity during cue-induced processing, while changes in its function may serve as a marker of subsequent alcohol relapse [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Consistent with prior studies (Garrison et al, 2016; Zakiniaeiz et al, 2017), connectivity analysis focused on the 2.5-minute imagery period (2-minute script and 0.5-minute quiet imagery), where the same cue trial imagery periods were concatenated for a total of approximately 5 minutes of data for each cue state.…”
Section: Methodsmentioning
confidence: 99%